Career resources in higher education: Characterization and diagnosis of pyschoeducational needs - Monteiro, Sílvia (2022)
Hirschi and colleagues [1] propose a comprehensive framework to assess key predictors of career success based on meta-analytic research. Four types of career resources, defined as “anything that helps an individual attain his or her career goals” (p. 4), are identified as predictors of subjective and objective career success. Those resources integrate key predictors for objective and subjective career success and specified 13 dimensions that are well established in the international career literature as predictors of career success. One crucial question arising from this theoretical proposal is to what extent different career resources can be fostered through e-learning, and what is the effect of such development? This study aims to contribute to responding to that question. A preliminary study was conducted to assess career resource needs among higher education students, in order to conceptualize and develop a distance career intervention program. For the diagnosis of needs, the Career Resources Questionnaire (CRQ) [2], adapted from Hirschi and colleagues [1], composed of twelve dimensions – Occupational Expertise; Job Market Knowledge; Soft Skills; Organizational Career Support; Study Challenge; Social Career Support; Career Involvement; Career Confidence; Career Clarity; Networking; Career Exploration; Learning –, was applied to 1898 students from the 1st, 3rd and 5th year of different graduation degrees of two Portuguese universities. Most participants identify themselves with the feminine gender (67.7%), and their ages range from 17 to 74 years old (M = 23.33, SD = 8.52). Part of the students is engaged in a paid professional activity (24.5%). The percentage of students with special educational needs is 1.8%. Descriptive and inferential statistics of the collected data were computed in order to inform the intervention planning about: (I) the career resources with higher and lower scores among the total sample; (ii) the correlation between the different career resources dimensions; (iii) the potential needs related to singular characteristics (social and cultural background, course year, institution, professional experience, and special education needs). The obtained results indicated higher scores for the dimensions of Social Support, Study Challenge, and Course Involvement. Lower scores were identified in the dimensions of Market Knowledge, Career Exploration and Institutional Support. The CRQ dimensions were positively correlated with each other, which means an overall need for a homogeneous intervention across the dimensions was identified as relevant. Regarding singular characteristics, differences were identified according to course year and professional experience.